CALCIUM ADSORPTION AT THE RUTILE-WATER INTERFACE: A POTENTIOMETRIC STUDY IN NACL MEDIA TO 250°C - INTERFACIAL AND INTERSPECIES PROCESSES - Ridley M.K.; Machesky M.L.; Wesolowski D.J.; Palmer D.A. (My University, 1999)
Calcium adsorption by rutile was studied potentiometrically from 25 to 250°C, at ionic strengths of 0.03 and 0.30 m in NaCl media, using two complementary experimental methodologies. In the first, net proton adsorption in the presence and absence of Ca2+ was monitored, and in the second, samples were periodically withdrawn during the course of a titration to determine Ca2+ adsorption directly. These experiments revealed that Ca2+adsorption systematically increased with temperature relative to the pH of zero net proton charge in NaCl media alone (pHznpc(NaCl) - pH). That is, as temperature increased, Ca2+ adsorption commenced at progressively more positive pHznpc(NaCl) - pH values. Increasing ionic strength from 0.03 to 0.30 m NaCl suppressed Ca2+ adsorption at all temperatures as a result of either increased competition from Na+ or greater complexation of Ca2+ by Cl-. Finally, there was no apparent trend in the proton stoichiometric ratios (moles H+ released / moles Ca2+ adsorbed) with increasing temperature. This suggests that the electrostatic and/or chemical processes involved in Ca2+ adsorption do not change greatly with increasing temperature. Favorable entropic effects, related to the increasing ease of releasing Ca2+ waters of hydration, are believed to be primarily responsible for the increase in adsorption with temperature.